2016
DOI: 10.1086/688315
|View full text |Cite|
|
Sign up to set email alerts
|

Pulmonary Vascular and Ventricular Dysfunction in the Susceptible Patient (2015 Grover Conference Series)

Abstract: Pulmonary blood vessel structure and tone are maintained by a complex interplay between endogenous vasoactive factors and oxygen-sensing intermediaries. Under physiological conditions, these signaling networks function as an adaptive interface between the pulmonary circulation and environmental or acquired perturbations to preserve oxygenation and maintain systemic delivery of oxygen-rich hemoglobin. Chronic exposure to hypoxia, however, triggers a range of pathogenetic mechanisms that include hypoxia-inducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 180 publications
(238 reference statements)
1
9
0
Order By: Relevance
“…In addition, it has been shown that myocardial pressure overload from hypertension can induce IL-33 production by cardiovascular endothelial cells [ 26 ], which may induce local or even systemic inflammation. Here, exposure of WT mice to hypoxia induced obvious right, but not left ventricular hypertrophy as verified by alterations in single cardiomyocyte diameter, while knockdown of St2 significantly abrogated this phenomenon, clearly implicating the IL-33/ST2 axis in the pathogenesis of HPH and consequent right heart failure.There are already several studies in the literature implicating HIF-1α and VEGF in the pathogenesis of the vascular remodelling which results in HPH [ 1 , 2 ]. Increased expression of HIF-1α has been noted in the serum of patients with HPH and in the lungs in animal models [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been shown that myocardial pressure overload from hypertension can induce IL-33 production by cardiovascular endothelial cells [ 26 ], which may induce local or even systemic inflammation. Here, exposure of WT mice to hypoxia induced obvious right, but not left ventricular hypertrophy as verified by alterations in single cardiomyocyte diameter, while knockdown of St2 significantly abrogated this phenomenon, clearly implicating the IL-33/ST2 axis in the pathogenesis of HPH and consequent right heart failure.There are already several studies in the literature implicating HIF-1α and VEGF in the pathogenesis of the vascular remodelling which results in HPH [ 1 , 2 ]. Increased expression of HIF-1α has been noted in the serum of patients with HPH and in the lungs in animal models [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic pulmonary hypertension (HPH) is commonly observed in the context of chronic hypoxia caused by a variety of lung diseases [ 1 , 2 ]. Although the precise mechanisms of HPH are largely unknown, hypoxia enhanced pulmonary vasoconstriction and vascular remodelling are considered to be the two major pathogenic processes of HPH, resulting in elevated pulmonary vascular resistance and consequent pulmonary artery pressure with eventual cardiac hypertrophy and failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polypeptide N -acetyl-galactose-aminyl-transferase 13 ( Galnt13 ) was also downregulated (−2.7-fold). Galnt is also downregulated in the blood of sickle-cell disease patients with pulmonary hypertension and could distinguish patients with and without increased RVSP with 100% accuracy [ 64 ]. Moreover, genetic association comparing patients with normal versus elevated tricuspid regurgitation jet velocity and pulmonary hypertension revealed 5 single nucleotide polymorphisms within this gene [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…44 Work evaluating the pathobiology of people living at high altitude provides insight into the role of genetic variation and response to hypoxia. 45 Novel research suggests that adverse perinatal events, including pre-eclampsia or periods of fetal hypoxia, could trigger a cascade of epigenetic events conferring a risk of subsequent pulmonary vascular disease. 46 This line of research is interesting and relevant, because there are known racial disparities in neonatal and perinatal mortality.…”
Section: Pathophysiological Differences Between Races In Pahmentioning
confidence: 99%